Metaverse: Improving the Quality of Indonesian Education in the Era of Society 5.0 - Mahfud Heru Fatoni; Baron Santoso; Hamid Syarifuddin; Slamet Budiyono (UNIVERSITAS SERAMBI MEKKAH, 2024)
Paper-based learning media is starting to be replaced by digital-based learning media. This research discusses the metaverse which can be used as a learning medium in the era of society 5.0 in order to improve the quality of Indonesian education in the future. The method used in this research is a literature study, in which researchers collect library data from relevant and up-to-date scientific journal sources. The research results show: 1) the metaverse is developing massively, considering that the metaverse is an interconnected social network. The implementation of metaverse in the world of education has a huge opportunity to support the learning process even better. 2) Metaverse can create a learning experience that is better, more inclusive, up to date, and more relevant to future demands. 3) Metaverse provides many benefits, including more interactive learning, effective training and development, a better learning experience, enabling distance/online learning, enhancing a more enjoyable learning experience, personalizing learning, learning visualization, Game-Based learning, Role Play and Perspective taking. 4) By understanding the advantages and disadvantages of using Metaverse, educators can plan appropriate steps to integrate this technology into modern education, thereby achieving an increase in the quality of education in Indonesia.